The role of Islamic lifestyle on social security in Russia - Ivanova, Tatyana N. (HTS teologiese studies, 2021)
Despite the historical realm of security, this concept has been proposed as a social issue only in the modern era and has been tried to be studied empirically. In fact, Islam has considered social security as an important principle in human life and has made other issues dependent on social security. Therefore, the most important issue of urbanisation is social security. Those who commit social offences often do not have a positive view of their society and sometimes of the whole creation and regard social systems and sometimes the universe unhealthy and deviating. In addition, they think that they cannot obtain their true right in an acceptable and natural routine. Islam, along with warning and fear, which can eliminate the root and origin of sin and deviation, has emphasised and encouraged the heavenly reward and worldly happiness. Therefore, the present study aimed to determine the role of Islamic lifestyle in social security in Volga Region in Russia. Hence, 10 000 citizens were selected as the statistical population by simple random sampling method. The data have been analysed by Linear Structural Relations (LISREL) software. The participants’ opinions indicated that the Islamic lifestyle plays a significant role in improving social security (P = 0.756; T = 12.453). Therefore, by implementing Islamic teachings in their lives, one will not only have a balanced and meaningful personal life but also security, order and participation will establish social life and society.Contribution: This article contributes to the role of Islamic lifestyle in social security in Volga Region in Russia.